Test of protease activity on pigeon pea beans (Cajanus cajan (L.) Millsp.) fermented by Aspergillus niger - Pujiati Pujiati; Cicilia Novi Primiani (The East Java Biological Society, 2018)
The objective of this study is to establish the effect of inoculum concentration and incubation time of protease activity on pigeon pea beans fermented by Aspergillus niger. The study comprises two independent variables: the inoculum concentration of Aspergillus niger, which consists of four levels (0 mL/g; 0.2 mL/g; 0.4 mL/g, and 0.6 mL/g), and six levels of incubation time (0 h, 24 h, 48 h, 72 h, 96 h, and 120 h). The obtained data were tested using two-way analysis of variance (ANOVA) followed by an LSD test with a significance level of 5%. The results show that the inoculum concentration of Aspergillus niger and incubation time do affect the activity of the protease enzyme. The highest enzyme activity of 0.298 U/ml was obtained at an inoculum concentration of Aspergillus niger of 0.4 mL/g, with an incubation time of 96 h (P2K4).